Managing Chronic Inflammation in the Aging Diabetic Patient With CKD by Diet or Sevelamer Carbonate: A Modern Paradigm Shift - Vlassara, H. (Oxford University Press, 2012)
The maintenance of normal metabolism and body defenses depends on the balance between cellular antioxidant and anti-inflammatory factors. This balance can be disrupted by agents/mechanisms in the extracellular milieu that induce excess reactive oxygen species (ROS) and inflammation. Cytopathic advanced glycation endproducts, present in ever increasing amounts in the modern diet, are one of the major environmental factors that cause excess ROS and/or inflammation at all ages and induce complications in aging, such as chronic kidney disease (CKD) and type 2 diabetes. Increased ROS and/or inflammation are present in both aging and CKD, and are associated with reduced cellular defenses against ROS and/or inflammation. Affected individuals have reduced defenses against further stress and are predisposed to organ failure, now a well-known phenomenon in aging. Thus, new methods are urgently needed to safely reduce ROS and/or inflammation in the aging type 2 diabetes patient with CKD. Studies of both normal aging and diabetic patients with kidney disease underline the fact that increased ROS and/or inflammation can be managed in these conditions by economical, safe, and effective interventions that reduce the uptake of advanced glycation endproducts by either modifying preparation of food or an oral drug. This communication reviews these data and adds new information on the efficacy of a drug, sevelamer carbonate, required to reduce ROS and/or inflammation in the aging type 2 diabetes patient complicated by CKD. If larger and longer studies confirm the hypothesis that one or both of these interventions reduce progression of CKD, it could represent a new paradigm in the management of complications in the type 2 diabetes patient with CKD.